IMPLEMENTASI KEBIJAKAN OLEH UPT PERLINDUNGAN PEREMPUAN DAN ANAK (PPA) DI KOTA PEKANBARU TERHADAP PENANGANAN ANAK KORBAN KEKERASAN DALAM RUMAH TANGGA TAHUN 2023 - Rahmawati, Tri; ,, Adlin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2025)
This research is motivated by domestic violence, particularly violence against children. This is because many child victims or other family members do not report the violence they experience. Children are a trust and a gift from God Almighty, who must always be protected because they are inherently endowed with dignity, and human rights that must be upheld. Child protection is not only the responsibility of the government, but also of parents and the community. Given the limited budget and human resources available in relevant agencies, it is hoped that the community and parents will also increase their awareness of providing child protection. This research was conducted at the Technical Implementation Unit for the Protection of Women and Children (PPA) in Pekanbaru City. The purpose of this study was to describe the implementation of the PPA Technical Implementation Unit's duties in handling child victims of domestic violence in 2023. This study used a qualitative approach and descriptive research. Data collection techniques were conducted through interviews and documentation. This study utilized George C. Edward III's Implementation Theory, with indicators of communication, resources, disposition, and bureaucratic structure. The research found that the implementation of tasks in handling reported cases is suboptimal. This is due to several obstacles, including a lack of human resources, inadequate facilities and infrastructure for program implementation, and limited budget. The implementation of the Technical Implementation Unit (UPT PPA) still faces challenges that require cross-sectoral attention. More intensive coordination is needed between the UPT PPA (Principal Implementation Unit) and related agencies to strengthen the protection system and expedite the response to each report of domestic violence. These findings are expected to provide evaluation material and considerations in formulating more effective and responsive policies for the protection of child victims of domestic violence. Keywords: Children, Domestic Violence,UPT